(untitled) (The International Journal for Scientific Research, 2024)
This study aimed to explore the impact of perceived operational risks (supply chain disruptions, food safety, and IT - technological risks) on customer satisfaction at Panda Retail Company in Saudi Arabia. Utilizing a descriptive, survey-based approach, data was collected from a random sample of 100 Panda customers through an online questionnaire. The findings revealed that 76% of customers acknowledge the negative impact of essential product shortages on the perceived value of service, with 79% expressing frustration when encountering seasonal product shortages. Regarding food safety risks, 72% of customers emphasized the detrimental effect of non-compliance with hygiene standards on their satisfaction, while 73% indicated that the presence of expired products diminishes the service value. Although 81% of customers expressed overall satisfaction with their shopping experience at Panda, only 62% were satisfied with product prices. Furthermore, 76% of customers recognized the impact of electronic payment system malfunctions on service value, and 65% expressed concern over potential personal data loss due to technical glitches. The study concluded that a statistically significant but weak relationship exists between perceived operational risks and customer satisfaction, indicating other factors might influence customer satisfaction. Based on these findings, the study recommends Panda to enhance supply chain management to ensure product availability, tighten food safety control measures across all stores, invest in technological infrastructure to guarantee stable and secure electronic systems, and strengthen loyalty programs and effective communication with customers.